A case study of applying gamification tools in business mathematics for higher education students - Lawrance, Paul Joseph (2022)
Empirical research was conducted on applying Gamification in Higher Education using the dynamics and mechanics of gaming in a non-game context of the subject Business Mathematics for undergraduate students. A case study was used as a method to collect data using questionnaires, observations, and interviews. Online feedback was conducted as part of the semester completion for the subject Business Mathematics to test the usage of Gamification tools (Kahoot!, Socrative, Quizlet, Quizizz and Showbie) in learning. It was found that Gamification tools enhanced students’ motivation in learning and understanding mathematical concepts, and that it has boosted their engagement in gamification activities, increased critical thinking and problem-solving skills.